Application of Management Accounting Tools in Non-Life Insurance Companies of Nepal - Singh, Prem Bahadur (Far Western Review, 2024)
This study investigates the application of management accounting tools in non life insurance companies in Nepal, focusing on tools such as budgeting, variance analysis, and cost-volume-profit (CVP) analysis. The research examines how these tools are used to improve decision-making, cost management, and financial performance within the sector. A mixed-methods approach is employed, combining quantitative data analysis with qualitative insights from interviews with financial managers from selected companies. Findings reveal that budgeting and variance analysis are commonly utilized, contributing positively to managing operational costs and enhancing profitability. However, more advanced tools like activity-based costing (ABC) and balanced scorecards are less frequently adopted, limiting the potential for optimizing financial strategies and long-term planning. The study highlights the need for broader adoption of advanced management accounting tools and recommends integrating these tools into strategic planning processes. Enhancing the financial teams’ skills through training could further strengthen financial management practices, supporting the growth and stability of Nepal’s non-life insurance sector.